CHARACTERISTICS OF AC-ECM SIGNALS OBTAINED BY USE OF THE VESTFONNA ICE CORE, SVALBARD - マツオカ, ケンイチ; ナリタ, ヒデキ; スギヤマ, ケン; マトバ, スミト; モトヤマ, ヒデアキ; ワタナベ, オキツグ; MATSUOKA, Kenichi; NARITA, Hideki; SUGIYAMA, Ken; MATOBA, Sumito; MOTOYAMA, Hideaki; WATANABE, Okitsugu (National Institute of Polar Research, 1997)
P(論文) AC-ECM measurements of the Vestfonna ice core were carried out under the following conditions : at -12,-17,-22 and -27℃ under 1MHz; at -22℃ under frequencies from 300kHz to 1MHz. The relationship between conductance measured with AC-ECM and acidity was linear. It is considered that salt impurities also affect to the AC-ECM signals. However, we focus on the effect of acidity, because it is known that the effect of acid on the a. c. conductance is 3.6 times as large as that of salt from DEP analysis of the Dolleman ice core. The intercept of the linear regression is coincident with the conductance of pure ice; at -23℃, it is 3.6nS. The gradient, conductance increases raised acid, is 0.70nS l/μmol at -23℃. The gradients at four temperatures were well fitted with the Arrhenius equation and activation energy is 24.8kJ/mol. Activation energy obtained from this study, the Dolleman ice core and acid-doped ice agree with each other within the error range. The conductance at -22℃ increases monotonically from 300kHz to 1MHz. This tendency is not caused by the system but by impurities in the specimen. The ratio between the conductance at 300kHz and at 1MHz is 0.845. This can not explain with one Debye dispersion. These results add basic knowledge for radio-echo soundings, especially at percolation zone in the ice cap. departmental bulletin paper